2021
DOI: 10.1002/aur.2583
|View full text |Cite
|
Sign up to set email alerts
|

Use of allied‐health services and medication among adults with ASD in Latin America

Abstract: ASD is a neurodevelopmental disorder that affects people across the entire lifespan, yet most of the research identifying the health and medical needs for autistic individuals have been among minors. As individuals with ASD transition to emerging adulthood, the services, already limited, become less available. This study aimed to identify the use of services for Latin American adults on the spectrum. We surveyed 295 caregivers of adults with ASD from six Latin American countries. Comparing the results for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(110 reference statements)
0
4
0
1
Order By: Relevance
“…Prior to the pandemic, in a study of six Latin American countries, 19% of children and adolescents with autism had failed to receive any kind of service during their lifetime (Montiel-Nava et al, 2020). Complementing this study, Torres et al (2021) found that 84.4-95.9% of adults were receiving zero hours per week. When these disparities are compounded by a global crisis of the magnitude of COVID-19, it compromises the continuation of services for this highly vulnerable population (Pellicano & Stears, 2020) and there is a risk of exponentially increasing inequities in access to services for people with autism in Mexico.…”
Section: Discussionmentioning
confidence: 65%
“…Prior to the pandemic, in a study of six Latin American countries, 19% of children and adolescents with autism had failed to receive any kind of service during their lifetime (Montiel-Nava et al, 2020). Complementing this study, Torres et al (2021) found that 84.4-95.9% of adults were receiving zero hours per week. When these disparities are compounded by a global crisis of the magnitude of COVID-19, it compromises the continuation of services for this highly vulnerable population (Pellicano & Stears, 2020) and there is a risk of exponentially increasing inequities in access to services for people with autism in Mexico.…”
Section: Discussionmentioning
confidence: 65%
“…Demographic and socio-economic variables were included. The age groups were 1-5 years, 6-11 years, 12-17 years, 18-25 years, 26 years and over, referring to the previous studies (Malik-Soni et al, 2022;Torres et al, 2021).The sex included male and female. The ASD types were AD; AS; PDD-NOS.…”
Section: Methodsmentioning
confidence: 99%
“…The survey used different questions to inquire about the child’s language and symptom severity. Complete information on the development and properties of the survey is given in the works of Torres et al (2021), Paula et al (2020), and Montiel-Nava et al (2020).…”
Section: Instrumentmentioning
confidence: 99%